2020
DOI: 10.1007/s00709-019-01442-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain ribosomal protein trees and the planctobacterial origin of neomura (eukaryotes, archaebacteria)

Abstract: Palaeontologically, eubacteria are > 3× older than neomura (eukaryotes, archaebacteria). Cell biology contrasts ancestral eubacterial murein peptidoglycan walls and derived neomuran N-linked glycoprotein coats/walls. Misinterpreting long stems connecting clade neomura to eubacteria on ribosomal sequence trees (plus misinterpreted protein paralogue trees) obscured this historical pattern. Universal multiprotein ribosomal protein (RP) trees, more accurate than rRNA trees, are taxonomically undersampled. To re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 519 publications
(1,008 reference statements)
2
61
1
Order By: Relevance
“…For instance, lipopolysaccharides (LPS) have not been detected in C. aurantiacus and O. trichoides (Knudsen et al, 1982;Meissner et al, 1988;Keppen et al, 2018). Moreover, crucial genes of the LPS biosynthesis pathway have not been found in Chlorolexales or in other Chloroflexota species (Cavalier-Smith, 2006;Sutcliffe, 2010;Antunes et al, 2016;Keppen et al, 2018). In addition, we also analyzed Chloroflexota genomes, including the newly described "Ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, lipopolysaccharides (LPS) have not been detected in C. aurantiacus and O. trichoides (Knudsen et al, 1982;Meissner et al, 1988;Keppen et al, 2018). Moreover, crucial genes of the LPS biosynthesis pathway have not been found in Chlorolexales or in other Chloroflexota species (Cavalier-Smith, 2006;Sutcliffe, 2010;Antunes et al, 2016;Keppen et al, 2018). In addition, we also analyzed Chloroflexota genomes, including the newly described "Ca.…”
Section: Resultsmentioning
confidence: 99%
“…The architecture of the multilayered cell envelope of Chloroflexota has been a source of debate for a long time. Among others, some points of contention have centered around some micrographs that arguably do not allow to undoubtedly determine discrete layers in the cell envelope ( Cavalier-Smith, 2006 ; Sutcliffe, 2011 ; Cavalier-Smith and Chao, 2020 ). Our tomograms revealed that both “ Ca .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger bacterial tree ( Fig. 5 ) results from an extremely aggressive selection ( Table 1 , B) but it still shows what we consider as the main groups of Bacteria (Proteobacteria, PVC, FBC, and “monoderm” phyla) and, after accounting for the idiosyncratic taxon names, most groups described by T. Cavalier-Smith ( Cavalier-smith & Chao, 2020 ) are visible (with the exception of Eoglycobacteria and Hadobacteria, which were both absorbed in polyphyletic groups). Regarding the topology of the tree, all the organisms from the main super-phyla are generally regrouped in the same subtree, with some exceptions.…”
Section: Resultsmentioning
confidence: 84%
“…The larger bacterial tree ( Figure 5) results from an extremely aggressive selection ( Table 1, B) but it still shows what we consider as the main groups of Bacteria (Proteobacteria, PVC, FBC, and monoderms phyla) and, after accounting for the idiosyncratic taxon names, most groups described by T. Cavalier-Smith 41 are visible (with the exception of Eoglycobacteria and Hadobacteria, which were both absorbed in polyphyletic groups).…”
Section: Application Example Of Tqmdmentioning
confidence: 87%